Increased Early Systemic Inflammation in ICU-Acquired Weakness; A Prospective Observational Cohort Study*. Issue 6 (June 2017) - Witteveen, Esther; Wieske, Luuk; van der Poll, Tom; van der Schaaf, Marike; van Schaik, Ivo N.; Schultz, Marcus J.; Verhamme, Camiel; Horn, Janneke
Abstract : Objectives: To investigate whether patients who develop ICU-acquired weakness have a different pattern of systemic inflammatory markers compared with critically ill patients who do not develop ICU-acquired weakness. Design: Prospective observational cohort study. Setting: Mixed medical-surgical ICU of a tertiary care hospital in the Netherlands. Patients: Newly admitted critically ill patients, greater than or equal to 48 hours on mechanical ventilation with a nonneurologic ICU admission diagnosis, were included. Interventions: A panel of systemic inflammatory markers and soluble vascular adhesion molecules were measured in plasma samples of day 0, 2, and 4 after ICU admission. ICU-acquired weakness was diagnosed by manual muscle strength testing as soon as patients were awake and attentive. Measurements and Main Results: Ninety-nine of 204 included patients developed ICU-acquired weakness. Principal component regression analysis, adjusted for confounders, showed that principal component 1, mainly loaded with interleukin-6, interleukin-8, interleukin-10, and fractalkine, was significantly higher in patients who developed ICU-acquired weakness (odds ratio, 1.35 [95% CI, 1.18–1.55]). Partial least squares-discriminant analysis also showed that these markers were the most important discriminative markers. Mixed-effects models of these markers showed that ICU-acquired weakness was associated with an independent 1.5- to two-fold increase in these markers. Conclusions: Systemic inflammation is increased in patients who develop ICU-acquired weakness compared with patients who do not develop ICU-acquired weakness in the first 4 days after ICU admission. This finding is consistent when adjusted for confounders, like disease severity. A group consisting of interleukin-6, interleukin-8, interleukin-10, and fractalkine was identified to be the most important. Abstract : Supplemental Digital Content is available in the text.